(untitled) (The Review of Diabetic Studies, 2025)
Healthcare-associated infections (HAIs) remain one of the most persistent challenges facing modern healthcare systems, contributing to preventable morbidity, mortality, and financial burden. This review examines multidisciplinary strategies that unify the roles of medical, surgical, diagnostic, and supportive departments to strengthen infection prevention and control (IPC) programs across hospital settings. Evidence from recent studies demonstrates that effective IPC relies on synergy among frontline clinical teams, laboratory diagnostics, pharmacy antimicrobial stewardship, environmental services, infection control committees, and health information systems. Multidisciplinary coordination enhances surveillance accuracy, accelerates outbreak detection, improves adherence to hand hygiene and isolation protocols, and supports antimicrobial optimization. The review synthesizes best practices, operational models, and collaborative mechanisms that collectively reduce HAIs, including MRSA, C. difficile, ventilator-associated pneumonia (VAP), catheter-associated urinary tract infections (CAUTI), and surgical-site infections (SSI). Findings highlight that unified departmental integration significantly improves patient safety outcomes, workflow efficiency, IPC compliance culture, and organizational readiness for emerging infectious threats. Practical recommendations are proposed to support healthcare leaders in transitioning toward a hospital-wide, multidisciplinary IPC model.